Increasing financial literacy capacity and long-term investment of indonesian migrant workers in malaysia - Supriyono, Bambang; Muluk, Mujibur Rahman Khairul; Ari, Dessanti Putri Sekti; Latifah Hanum; Dhefara Hersaning Djati (Journal of Community Service and Empowerment, 2026)
The low level of financial literacy and understanding of long-term investment among Indonesian Migrant Workers (PMI) in Malaysia is a serious problem that impacts consumptive income management and minimal post-migration financial planning. This condition has the potential to hinder the sustainability of PMI's welfare after returning home. This activity aims to improve the capacity of financial literacy and understanding of long-term investment for PMI in Malaysia through an educational and participatory approach. The activity was implemented through a collaboration between the Faculty of Administrative Sciences, Brawijaya University and the Indonesian Embassy (KBRI) in Kuala Lumpur. The methods used included Focus Group Discussions with the Indonesian Embassy's Labor Attaché, material delivery through lectures, interactive discussions, and direct mentoring related to financial management and investment. The activity evaluation used a one-group pretest and posttest design to measure changes in participants' level of understanding. The evaluation results showed a significant increase in knowledge, with an average N-Gain Score of 0.75, which is considered high, and an activity effectiveness level of 75 percent, which is considered quite effective. Overall, this activity had a positive impact in increasing PMI's awareness and understanding of the importance of long-term financial management and investment as a foundation for sustainable prosperity in the future